Fall–winter cover crops promote soil health and weed control in the southeastern clayey soils. (16th January 2023) - St Aime, Ricardo; Bridges, William C.; Narayanan, Sruthi
Abstract: Seven winter cover crops including grasses, legumes, and brassicas were evaluated for biomass production and effects on weed presence, stored soil water, soil health indicators, and the performance of a subsequent soybean [ Glycine max (L.) Merr.] crop in the clayey soils of South Carolina during 2019–2020 and 2020–2021. A mixture of Austrian winter pea ( Pisum sativum L.), rye ( Secale cereale L.), crimson clover ( Trifolium incarnatum L.), hairy vetch ( Vicia villosa Roth), and oat ( Avena sativa L.), a mixture of crimson clover and rye, and single rye ranked high for biomass production. Cover crops did not deplete more soil water than a fallow did (–22 to 8% difference in soil water retention, compared to fallow with or without herbicide application), controlled weeds equally well or better than herbicides (>90% reduction in weed presence, compared to herbicide control), and reduced soil penetration resistance (>40%, compared to fallow with or without herbicide application in the second season). The five‐species mixture also improved soil biological activity (>43% increase in soil respiration at cover‐crop termination, compared to that under a chemical fallow). The subsequent soybean crop's yield was never negatively affected if not improved by the above cover crops (9–173% increase, compared to that following a chemical fallow). Our results indicate the suitability of the above cover crops for the southeastern clayey soils based on biomass production, weed suppression, and improvements in soil health and the subsequent soybean crop's performance and provide the rationale for planting them rather than keeping the land under a chemical fallow. Core Ideas: We found two‐ and five‐species grass‐legume mixtures that produced the same amount of biomass as rye. The above mixtures and rye did not deplete more soil water than a fallow did. All three suppressed weeds, reduced soil penetration resistance, and maintained or improved subsequent soybean yield. The five‐species mixture also enhanced soil biological activity relative to a fallow. Our results demonstrate the advantage of fall‐winter cover crops over keeping the land under a chemical fallow.